1997
DOI: 10.1063/1.120060
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-size effects in the titanosilicate molecular sieve

Abstract: The recently synthesized Engelhard titanosilicate (ETS-10) represents a material which contains in the structure well defined atomic ⋯O–Ti–O–Ti–O⋯ quantum wires embedded in a highly insulating siliceous matrix. We report and discuss the UV-Vis spectrum of this material and compare the experimentally determined optical band gap with the results predicted by simple modeling of a titanium oxide semiconductor wire unidimensionally confined by an infinite potential barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
118
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 25 publications
7
118
2
Order By: Relevance
“…The spectrum of this sample ( Fig. 7(a)) shows a sharply defined absorption edge at about 4.0 eV, in good agreement with the calculated band gap [28] and previously reported spectra [27,28]. Also shown is the spectrum of a commercially prepared sample of ETS-10 supplied by Engelhard Corporation.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The spectrum of this sample ( Fig. 7(a)) shows a sharply defined absorption edge at about 4.0 eV, in good agreement with the calculated band gap [28] and previously reported spectra [27,28]. Also shown is the spectrum of a commercially prepared sample of ETS-10 supplied by Engelhard Corporation.…”
supporting
confidence: 80%
“…Attention has been drawn recently to the unusual optical properties shown by a novel titanosilicate zeolite structure ETS-10 (Na2TiSi~O13) in which one dimensional chains of TiO6 octahedra imbedded in a microporous siliceous network exhibit quantum size effects [27,28]. The structure of ETS-10 is represented in Fig.…”
mentioning
confidence: 99%
“…The m z value may be much smaller if the l value of the TiO 3 2À molecular wire in E-0.3 is longer than 50 nm, which is also possible. If the l value for E-0.3 is assumed to be as small as 25 nm, as estimated by others, [16][17][18] the m z value from the fit is 0.0027 m e , which is still much smaller than the smallest values yet reported (for InSb, m z = 0.014 m e , [29] for carbon nanotubes, m z = 0.019 m e ; [30] Table SI-6). …”
mentioning
confidence: 94%
“…The combination of a wide band-gap semiconducting oxide [37][38][39][40] with a three-dimensional 12-membered ring microporous framework offers many potential advantages in photocatalysis, such as excellent diffusion of reactant molecules, trapping and, in particular, shape selectivity. As a high selectivity toward the photodegradation of large aromatic molecules has been observed, it has been concluded that molecules entering the pore system were protected from photodegradation, which occurred on the external surface on specific defects.…”
Section: Positioning Heterogeneous and Homogeneousmentioning
confidence: 99%